Potential development of community innovation for sustainable living: Foreign perspectives on the relationship between state, society, and industry - Akarapattananukul, Yared; Tantrajin, Patcharapa (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
The coexistence between public and industrial sectors, particularly in economic zones, tends to escalate a propensity for conflict due to competition over limited resources and the negative impact of state economic development policies on social structures and local communities. This research employs a qualitative methodology, with a primary focus on the systematic collection and analysis of documentary data. The objectives of the study are twofold: (1) to critically analyze community innovations implemented in different countries that facilitate coexistence between communities and industrial sectors; and (2) to develop insightful recommendations for empowering communities through the enhancement of their participatory capacity in community-driven innovation endeavors. By illustrating the development since the 20th century, the study encompasses both industrial countries, i.e., Taiwan and China, and post-industrial countries, i.e., the United States and Sweden. The findings of the study reveal that community innovations exhibit nuanced manifestations contingent upon the contextual factors, including history, political opportunities and spatial dynamics. However, a common thread among these divergent manifestations lies in the imperative of multi-stakeholder engagement within society and community participation. These innovative endeavors assume multifaceted forms, encompassing technological advancements, project initiatives, policy formations, governance processes, and developmental frameworks. In addition, recommendations for empowerment and capacity development of community-driven innovation can be addressed through the lens of four pertinent dimensions: (1) the contextual conditions for community innovations; (2) advantages leading to success in creating community innovations; (3) the challenges that may be obstacles to the development of community innovations; and (4) the driving forces to create community innovations.